2008
DOI: 10.1007/s11671-008-9116-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Magnetic Metal-encapsulated Multi-walled Carbon Nanobeads

Abstract: A novel, cost-effective, easy and single-step process for the synthesis of large quantities of magnetic metal-encapsulated multi-walled carbon nanobeads (MWNB) and multi-walled carbon nanotubes (MWNT) using catalytic chemical vapour deposition of methane over Mischmetal-based AB3alloy hydride catalyst is presented. The growth mechanism of metal-encapsulated MWNB and MWNT has been discussed based on the catalytically controlled root-growth mode. These carbon nanostructures have been characterized using scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…In addition to the above mentioned possibilities of applications, carbon nanostructures with metal-encapsulation find applications in electronic and biological fields [14]. The present works aims at synthesizing metal-encapsulated and graphitized carbon nanostructures in a simple and single heating process.…”
Section: Significance Of Carbon and Nanocarbonmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the above mentioned possibilities of applications, carbon nanostructures with metal-encapsulation find applications in electronic and biological fields [14]. The present works aims at synthesizing metal-encapsulated and graphitized carbon nanostructures in a simple and single heating process.…”
Section: Significance Of Carbon and Nanocarbonmentioning
confidence: 99%
“…The name "Helical" should be given to denote this type of nanotubes, however, in order to respect the definition of chirality, which makes all chiral molecules unable to be superimposed on their own image in a mirror, 'Chiral' is used [29]. [14,47].…”
Section: Structure Of Graphite Graphene and Nanotubesmentioning
confidence: 99%
“…Carbon-based material is one kind of the most important functional materials because of its unique electromagnetic, thermodynamical, and mechanical properties [1-3] that exhibit potential applications in many areas such as drug delivery, hydrogen storage, junction device, and sensors. Many attempts have been made in the synthesis of nanoparticles with shape control.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many studies focused on the synthesis of carbon colloids via the hydrothermal approach. For example, Wang et al [1] were the first to report the hydrothermal synthesis of hard carbon spheres by using sugar as a precursor through heat treatment at 190 °C for 5 h. Li et al [22] reported that the carbon spheres could be prepared with different sizes from 200 to 1,500 nm under different reaction times (2–10 h, at 160 °C). Later, Mi et al [25] demonstrated a high-temperature method to produce carbon microspheres with size of 1–2 μm by heating at 500 °C for 12 h in a sealed autoclave.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have paid great attention to carbon spheres, as they have significant application in the preparation of diamond films, lubricating materials, and special rubber additives, owing to their properties similar to fullerene and graphite [12-14]. However, harsh environment was necessary for the synthesis of these hollow carbon spheres up to now [15-18].…”
Section: Introductionmentioning
confidence: 99%